Analisis Penyelesaian Kesulitan Belajar Peserta Didik Menuju Pendidikan Berkualitas Terhadap Penerapan Program SDGs Nomor 4 - Rizkiani, Riza; T, Trimurtini (Yayasan Daarul Huda Kruengmane, 2024)
Strategies and methods are a way to improve the quality of education so that students become part of changes in education for the better. Schools can use strategic management to plan strategies to improve their quality. The factors underlying strategic management are analysis of various aspects, both internal and external, which is often called SWOT analysis (strengths, weaknesses, opportunities and threats). This analysis activity considers the strengths, weaknesses and internal environment of the school. In this article the author examines the resolution of students' learning difficulties by implementing the SDGs Number 4 program. The learning problems experienced by students originate from internal and external factors that influence their level of understanding. Internal factors come from within students, while internal factors come from outside students. Difficulties originating from within students (internal) include: students' health conditions, interest in learning, students' attitudes, habits, and students' lack of motivation in learning. Meanwhile, learning difficulties that originate from outside the student (internal) consist of: the school environment, the atmosphere of the home and living environment, and the influence of gadgets. As educators, teachers try to overcome this problem. Apart from the efforts made by teachers, several government efforts to address problems in the world of education include: SATAP, educational programs in the 3T area, and calistung. Quality education can be realized if problems in the world of education are handled well by professional staff. The SDGs achievement strategy is a method implemented by the government to improve the quality of education listed in the 4th SDGs goal, namely Quality Education that is fair and equitable and provides opportunities for lifelong learning for all age levels